1999
DOI: 10.1046/j.1365-2842.1999.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bonding agents on the microleakage and bond strength of sealant in primary teeth

Abstract: This in vitro study investigated the effect of use of three dentine bonding agents: Scotchbond Multi-Purpose Plus (3M Dental Products, St. Paul, Minnesota, U.S.A.), Syntac (Vivadent, Schaan, Liechtenstein), Optibond Dual Cure (Kerr, Romulus, MI, U.S.A.) on microleakage and shear bond strength of a fissure sealant (Helioseal F, Vivadent, Schaan, Liechtenstein) bonded to either dry or wet (saliva contaminated) enamels of primary teeth. Newly extracted 112 non-carious primary teeth were sectioned and embedded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 6 publications
3
24
0
5
Order By: Relevance
“…Over the last decades, the application of an intermediate bonding agent layer underneath the sealant has been widely suggested. The findings of several studies (4,6,(14)(15)(16)(17) have shown that the use of adhesive systems along with resin sealants may improve bonding to etched enamel under dry and contamination conditions. It is likely that solvents, such as ethanol and acetone, present in the currently available single-bottle adhesives are able to remove any residual moisture from the etched enamel, carrying the resin monomers into close adaptation with the surface (15,18).…”
Section: Subgroupsmentioning
confidence: 99%
“…Over the last decades, the application of an intermediate bonding agent layer underneath the sealant has been widely suggested. The findings of several studies (4,6,(14)(15)(16)(17) have shown that the use of adhesive systems along with resin sealants may improve bonding to etched enamel under dry and contamination conditions. It is likely that solvents, such as ethanol and acetone, present in the currently available single-bottle adhesives are able to remove any residual moisture from the etched enamel, carrying the resin monomers into close adaptation with the surface (15,18).…”
Section: Subgroupsmentioning
confidence: 99%
“…[5][6][7][8] However, technique errors and moisture contamination are still the major reason for sealant failure. [9][10][11][12][13][14] Sealing partially erupted molar teeth is a demanding procedure and in most cases is carried out using cotton roll isolation. Even if the contamination of the etched surfaces is not apparent, the sealant application under high relative humidity exhibited a significant reduction in its bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a bonding agent be placed before the sealant was applied, although there are many detractors to this application technique [5][6][7] . In some studies, it was said that application of bonding agent before fissure sealant increased the latter's effectiveness [8][9][10] . The study of Koyuturk et al 11) showed that application of bonding agent prior to application of fissure sealant yielded beneficial results in terms of microleakage.…”
Section: Introductionmentioning
confidence: 99%